Perkembangan dan Problematika Pasar Modal Syariah di Indonesia - Mohamad Toha; Agnes Agnes Cahyatria Manaku (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2020)
Investment is one of the efforts made in overcoming the problems of the Indonesian economy. Through the Islamic capital market sector with a variety of instruments in it able to provide new breakthroughs in the development of Indonesian Islamic finance and economic growth in Indonesia. At present the development of the Islamic capital market is very significant and continues to increase every year. In statistical data managed by the OJK, sharia shares have increased from the list of sharia securities recorded in 2013 by 328, rising to 445 in 2019. Likewise, sharia bonds and sharia mutual funds also continue to grow. Various challenges and obstacles faced in the development of Islamic capital markets ranging from regulation, literacy or public knowledge, to the lack of support from stakeholders in the Islamic capital market at this time are still coping with various efforts from both the IDX and the FSA that make the roadmap as strategies in developing the sharia capital market include regulating sharia capital market products, enhancing HR and information technology, working with the government and DSN-MUI to prove that transactions in the sharia capital market are in accordance with sharia principles. The roadmap is valid for 5 years ending in 2019. In 2020 OJK continues to undertake new efforts with the latest focus also in developing Islamic capital markets such as cooperating with MSMEs in enhancing the role of the capital market in financing the government sector.